Comparative Evaluation of Lipid Profile and C-Reactive Protein in Chronic Periodontitis and Coronary Heart Disease: Lipid Profile and C-Reactive Protein in Periodontitis and Heart Disease - Zehra, Afsheen; Tanwir, Farzeen; Ali, Sana Barkat; Ali, Hasan; Khan, Ali Nawaz; Bakhsh, Allah (Pakistan Journal of Health Sciences, 2024)
Epidemiological studies suggest local infections may elevate systemic inflammatory mediators and lipid levels, potentially promoting atherosclerosis. Objective: To investigate the correlation between Chronic Periodontitis (CP) and Coronary Heart Disease (CHD), assessing C-Reactive Protein (CRP) and lipid profile alterations in affected patients. Methods: This case-control study included 88 participants, divided into four groups: 22 with Chronic Periodontitis (CP), 22 with Coronary Heart Disease (CHD), 22 with both CP and CHD and 22 systemically healthy controls, aged 30-60 years, selected through consecutive sampling. Conducted at Bahria University Health Sciences and PNS Shifa Hospital from December 2022 to May 2023, the study assessed clinical and periodontal parameters, including probing depth and clinical attachment level. Fasting blood samples were analyzed for lipid profiles and C-Reactive Protein Levels. Statistical analysis included the Pearson Chi-square test for baseline demographics, the Kruskal-Wallis test for comparing biochemical and periodontal parameters, and the Spearman Rank Correlation. Results: Serum HsCRP levels were twice higher in participants with CP and CHD than in healthy individuals and three times higher in subjects with combined disorder (CP + CHD). Patients with both CP and CHD (CP + CHD) have the highest median CRP levels. C-reactive protein was negatively correlated with TC, LDL-C, HDL-C, and number of teeth, while positive correlations were demonstrated with PD, CAL, BoP%, and PI scores. Conclusion: Coronary heart disease and other inflammation driven atherosclerotic processes may be exacerbated by chronic infections, such as periodontitis, which can alter systemic levels of TC, HDL, LDL, and CRP.